1998
DOI: 10.1038/sj.onc.1201738
|View full text |Cite
|
Sign up to set email alerts
|

A cis-acting peptide signal in human immunodeficiency virus type I Rev which inhibits nuclear entry of small proteins

Abstract: A peptide signal, which may control nucleo-cytoplasmic protein tracking, was newly identi®ed in human immunode®ciency virus type I (HIV-1) Rev, a lentiviral post-transcriptional transactivator. The sequence, in the amino-terminal portion of HIV-1 Rev, maintains a Rev mutant with a dysfunctional nuclear/nucleolar targeting signal outside of the nucleus, although this Rev molecule itself is small enough to pass through the nuclear pores. Transition of this sequence to the N-terminus of human T-lymphocytic leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…However, we cannot completely exclude the possibility that, in addition to its anti-multimerization effect, in cells the nanobody exerts an extra anti-Rev activity that involves the same or overlapping Lys-20 and Tyr-23 residues. The N terminus of Rev is essential for Rev function and plays a role in its multimerization (17,24,25,47). The DEAD box helicase DDX1 is a co-factor that was also found to interact with the N terminus of Rev (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot completely exclude the possibility that, in addition to its anti-multimerization effect, in cells the nanobody exerts an extra anti-Rev activity that involves the same or overlapping Lys-20 and Tyr-23 residues. The N terminus of Rev is essential for Rev function and plays a role in its multimerization (17,24,25,47). The DEAD box helicase DDX1 is a co-factor that was also found to interact with the N terminus of Rev (48).…”
Section: Discussionmentioning
confidence: 99%
“…Domains in Rev that mediate splicing inhibition or translational activation either have not been defined or have been suggested to coincide with domains important for Crm1-dependent nuclear RNA export (9,22). As a result, it has not been possible to clearly address the functional relevance of these hypothetical Rev activities.…”
Section: Discussionmentioning
confidence: 99%
“…These groups have therefore suggested that Rev also activates the translation of RRE-containing HIV-1 transcripts. A proposed functional domain that allows the association of Rev with currently undefined cytoplasmic components and that coincides with sequences required for Rev multimerization could play a role in this hypothetical Rev activity (22). Finally, in addition to these two novel activities for Rev, it has also been suggested that other proteins, in addition to Crm1, can interact directly with Rev to promote nuclear mRNA export.…”
Section: Discussionmentioning
confidence: 99%
“…The NIS, a 15 amino acid peptide motif in the N-terminal of HIV-1 Rev, modulates nucleocytoplasmic protein trafficking and intracellular stability of the HIV-1 Rev [3][4][5]. When HIV-1 Rev enters the nucleus, the NIS stays around the nuclear membrane by behaving like an anchor and interferes with the nuclear entry of passive diffusion small proteins [3][4][5]. The NIS consists of an amphipathic helix, thought to allow binding to the lipid-bilayer of biomembranes, which include the nuclear membrane [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the existence of a nuclear diffusion inhibitory signal (NIS) has been recently identified. The NIS, a 15 amino acid peptide motif in the N-terminal of HIV-1 Rev, modulates nucleocytoplasmic protein trafficking and intracellular stability of the HIV-1 Rev [3][4][5]. When HIV-1 Rev enters the nucleus, the NIS stays around the nuclear membrane by behaving like an anchor and interferes with the nuclear entry of passive diffusion small proteins [3][4][5].…”
Section: Introductionmentioning
confidence: 99%